2012
DOI: 10.1080/14772019.2012.746589
|View full text |Cite
|
Sign up to set email alerts
|

The skull and neck of a new flagellicaudatan sauropod from the Morrison Formation and its implication for the evolution and ontogeny of diplodocid dinosaurs

Abstract: A new taxon of diplodocid sauropod, Kaatedocus siberi gen. et sp. nov., is recognized based on well-preserved cervical vertebrae and skull from the Morrison Formation (Kimmeridgian, Late Jurassic) of northern Wyoming, USA. A phylogenetic analysis places it inside Diplodocinae (Sauropoda: Flagellicaudata: Diplodocidae), as a sister taxon to a clade uniting Tornieria africana and the classical diplodocines Barosaurus lentus and Diplodocus. The taxon is diagnosed by a unique combination of plesiomorphic and deriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
181
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(187 citation statements)
references
References 57 publications
(120 reference statements)
2
181
4
Order By: Relevance
“…In mid-cervical vertebrae, the SPRL is weak to almost absent on the prezygapophyseal process, as is typical for Diplodocinae (Tschopp & Mateus, 2013b). Thus, the SPRF and SDF of anterior and mid-cervical vertebrae are not distinctly separated from each other at the base of the neural spine.…”
Section: Description Of Sma 0011mentioning
confidence: 68%
“…In mid-cervical vertebrae, the SPRL is weak to almost absent on the prezygapophyseal process, as is typical for Diplodocinae (Tschopp & Mateus, 2013b). Thus, the SPRF and SDF of anterior and mid-cervical vertebrae are not distinctly separated from each other at the base of the neural spine.…”
Section: Description Of Sma 0011mentioning
confidence: 68%
“…(B) Most parsimonious tree recovered after the inclusion of Leinkupal laticauda in another published data matrix focused on Diplodocidae relationships [22]. Support values (Bremer/Bootstrap) of principal nodes are in brackets.…”
Section: Resultsmentioning
confidence: 99%
“…tas et al, 1992). Bonaparte and Mateus (1999) defined a new diplodocid taxon, Dinheirosaurus alenquerensis, considered as a diplodocine form closely related to the North American Late Jurassic Supersaurus Whitlock, 2011;Mannion et al, 2012;Tschopp and Mateus, 2013;Tschopp et al, 2015). In fact, Tschopp et al (2015) suggested that Dinheirosaurus lourinhanensis might represent a species of Supersaurus, proposing the new combination Supersaurus lourinhanensis.…”
Section: Figurementioning
confidence: 99%